ATIM-08. A PHASE I TRIAL OF PEMBROLIZUMAB AND VORINOSTAT COMBINED WITH TEMOZOLOMIDE AND RADIATION THERAPY FOR NEWLY DIAGNOSED GLIOBLASTOMA (NCT03426891). (5th November 2018) - Sahebjam, Solmaz; Forsyth, Peter; Tran, Nam; Mokhtari, Sepideh; Arrington, John; Jaglal, Michael; Etame, Arnold; Liu, James; Wicklund, Melissa; Gatewood, Tyra; Macaulay, Robert; Robinson, Timothy; et al.
Abstract: BACKGROUND: A growing body of evidence indicates that epigenetic silencing of genes involved in antigen processing and immune recognition results in immune escape and resistance to immunotherapy. Pre-clinical experiments have shown that use of histone deacetylases inhibitors such as vorinostat can restore tumor immune recognition and synergize with anti-PD 1/PD-L1 antibodies. Moreover, vorinostat has radiosensitizing properties. This report describes an ongoing phase I trial of vorinostat in combination with an antibody against PD1 (pembrolizumab), radiotherapy and temozolomide (TMZ) in patients (pts) with newly diagnosed glioblastoma (GBM). METHOD: This study employs a standard 3 + 3 dose escalation design exploring 2 sequential dose escalation cohorts of vorinostat. Eligible pts are treated with concurrent radiotherapy (60 Gy in 30 fractions) with TMZ (75 mg/m 2 /day) followed by 6 cycles of maintenance TMZ. Pembrolizumab (200 mg) is administered intravenously once every 3 weeks. Dose level 1 is consistent of vorinostat 200 mg/day orally on days 1–5 every week during radiotherapy and 300 mg/day orally 1 week on 1 week off after radiotherapy. At dose level 2, pts receive 300 mg of vorinostat on days 1–5 every week during radiotherapy and 400 mg/day orally 1 week on 1 week off after radiotherapy. Once the recommended phase II dose (RP2D) of vorinostat is determined, an additional 20 pts will be enrolled in an expansion safety cohort. The primary study objectives are to determine safety and the RP2D of vorinostat administered with above combination in pts with GBM. Secondary endpoints include determination of the 12 and 24 month survival rates and exploring tissue and blood biomarkers. RESULTS: As of June 4, 2018, enrollment to dose level 1 has been completed. So far no does limiting adverse event has been observed. Thrombocytopenia and fatigue are the most common adverse events. Updated safety and efficacy results will be presented.